Motives for Participating in Sports Events Volunteering in Poland - Bańbuła Joanna (Sciendo, 2021)
In following paper, based on Clary et al.'s (1998) Volunteer Functions Inventory model, author wants to investigate which group of factors is the most and least important motive for participation in sports events volunteering in Poland for the study group. Data were collected in cooperation with two leading Academic Sports Federation - AZS Warszawa, AZS Kraków. 87 sports volunteers took part in the online survey.